KONTRIBUSI POWER OTOT LENGAN DAN DAYA TAHAN OTOT PERUT TERHADAP KECEPATAN RENANG 50 METER GAYA PUNGGUNG - Rasyiqa, Adzhani (2014)
Some of the physical condition component that affect the increase of speed for swimmers are arm muscle power and abdoment muscle endurance. Therefore, this research is about "The Contribution of Arm Muscle Power and Abdoment Muscle Endurance Towards 50 Meters Backstroke Swimming Speed". The method used in this researach is the descriptive method. Population this research is the backstroke athlete in Tirtamerta Swimming Club, and the samples are all 14 backstroke athletes, with using the total sampling technique. The instrument for this research are medicine ball-put test for arm power, sit-ups test for abdoment muscle endurance, and 50 meter backstroke swim for speed. Based on data proccess and analysis, the percentage point for arm muscle power is 67,44%, abdoment muscle endurance 56,12%, and both arm muscle power and abdoment muscle endurance 84,82%. The result for hypotheses test with paired skor test are 1) for arm power tcount 4,9853 ˃ ttable 2,18, therefore the arm muscle power is contributing significantly; 2) for abdoment muscle endurance tcount 3,9174 > ttable 2,18, therefore the abdoment muscle endurance is contributing significantly. For both arm muscle power and abdoment muscle endurance fcount 30,7319 > ftable 3,98, therefore both arm muscle power and abdoment muscle endurance are contributing significantly. The conclusion on this research are: arm muscle power and abdoment muscle endurance each contributing significantly towards the 50 meters swimming speed and both arm muscle power and abdoment muscle endurance together are also contributing significantly towards the 50 meters swimming speed